Halal training model for halal human capital development / Hanini Ilyana Che Hashim - Che Hashim, Hanini Ilyana (2021)
The halal industry has emerged as a new growth sector in the global economy. The demand for halal professional has increased after the introduction of the Malaysian Halal Certification for halal food industry which creates the needs for halal executives and auditors. Thus, halal training's and programs are needed for human resource development for the halal industry. However, the halal training programs vary in content, instructional delivery and time duration; and training's are one-off and without adequate assessment and evaluation. Additionally, there is no existing standard for proper halal training curricular structure; no review and approval on content coverage and duration of the halal training program; no evident-based assessment and evaluation of the training effectiveness; and lack of continual training and development program for halal human capital and career growth. Therefore, the main objective of this study was to develop a framework on halal training model for human capital development in Malaysia. The secondary objectives of this study are: 1) to identify current halal training providers and halal training programs; 2) to investigate the human capital development’s requirements to support halal industry; 3) to determine key determinants pertinent in halal training's for halal human capital development with respect to the Malaysian Standards MS2400 Halalan-toyyiban requirements. Qualitative research design was adopted for this study using in-depth interview with purposively-selected informants from halal stakeholders in Malaysia. Categories and themes were formulated based on coding analyses from the interview transcriptions. Analysis posited that the determinants on halal training's for halal human capital development are halal: knowledge; skills; shariah values; training objectives; curriculum design; training providers; and demand in halal management. Recommendations were put forth to improve the halal training's and continual development programs; and these shall serve as a reference for the halal stakeholders towards optimizing halal human capital development n in Malaysia. In conclusion, the research objectives had been achieved with the proposed model on halal training model for human capital development in Malaysia.